A Model of DC-DC Converter with Switched-Capacitor Structure for Electric Vehicle Applications - Filippo Pellitteri; Vincenzo Di Dio; Christian Puccio; Rosario Miceli (Energies, 2022)
In this paper, a DC-DC converter with an innovative topology for automotive applications is proposed. The goal of the presented power converter is the electrical storage system management of an electric vehicle (EV). The presented converter is specifically compliant with a 400 V battery, which represents the high-voltage primary source of the system. This topology is also able to act as a bidirectional power converter, so that in this case, the output section is an active stage, which is able to provide power as, for example, in the case of a low-voltage battery or a supercapacitor. The proposed topology can behave either in step-down or in step-up mode, presenting in both cases a high gain between the input and output voltage. Simulation results concerning the proposed converter, demonstrating the early feasibility of the system, were obtained in a PowerSIM environment and are described in this paper.